Pembandingan Model Pembelajaran Mind Mapping dan Arias (Assurance, Relevance, Interest, Assessment, Satisfaction) Terhadap Pemahaman Konsep Fisika - Rafika, Yeni; Anggraini, Welly; Fiah, Rifda El (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study aims to compare the Mind Mapping and ARIAS learning models (Assurance, Relevance, Interest, Assessment, Satisfaction) to the understanding of physics concepts in class VIII students at SMP Negeri 1 Bukit Kemuning. This study is a Quasi Experiment Design with research villages using the Pretest-Posttest Design Control Group. The selection of samples using Purposive Sampling techniques. The research samples were experimental class I (VIII 4) which applied the Mind Mapping learning model and experimental class II (VIII 6) which applied the ARIAS learning model (Assurance, Relevance, Interest, Assessment, Satisfaction). Data collection instruments used were test instruments for understanding concepts (pretest and posttest) with essay questions. Based on the research results that have been calculated by the t-test with a significant level of α = 0.05 (5%) that tcount = 1.725 and ttable = 1.708 which indicates that tcountmore than  ttable, to obtain conclusions Ha is accepted and H0 is rejected which means there is a comparison of models Mind Mapping and ARIAS on understanding the concepts of physics of students in SMP Negeri 1 Bukit KemuningAbstrak: Penelitian ini bertujuan untuk mengetahui perbandingan model pembelajaran Mind Mapping dan ARIAS(Assurance, Relevance, Interest, Assessment, Satisfaction) terhadap pemahaman konsep fisika pada peserta didik kelas VIII di SMP Negeri 1 Bukit Kemuning. Penelitian ini merupakan Quasi EksperimentDesign dengan desain penelitian menggunakan Pretest-Posttest Control Group Design. Pemilihan sampel menggunakan teknik Sampling Purposive. Sampel penelitian yakni kelas eksperimen I (VIII 4) yang diterapkan model pembelajaran Mind Mapping dan kelas eksperimen II (VIII 6) yang diterapkan  model pembelajaran ARIAS(Assurance, Relevance, Interest, Assessment, Satisfaction). Instrumen pengumpulan data yang digunakan yaitu instrumen tes untuk pemahaman konsep (pretest dan posttest) dengan bentuk soal essai. Berdasarkan hasil penelitian yang telah dihitung dengan uji-t dengan taraf signifikan α = 0,05 (5%) bahwa thitung = 1,725 dan ttabel = 1,708 yang menunjukkan bahwa thitunglebih dari  ttabel , sehingga diperoleh kesimpulan Ha diterima dan H0 ditolak yang artinya terdapat perbandingan model Mind Mapping dan ARIAS terhadap pemahaman konsep fisika peserta didik di SMP Negeri 1 Bukit Kemuning